Dietary diversity and anthropometric status of 6–36 months old children of Mumbai city - Apurva, P Agashe; Pangerkar, Pranali; Padmini, Ghugre; Shobha, A Udipi (Indian Journal of Child Health, 2018)
Background: Dietary diversity (DD) is an indicator of food security, accessibility, availability, and also a significant predictor of growth. Poor feeding practices are responsible for low DD which affects the nutritional status of child. Objective: The objective of the study was to assess the association of DD with nutritional status of urban slum children. Methodology: Data were collected using structured interview schedule on 823 children from 16 slums of western suburbs of Mumbai city. DD score was calculated using food frequency questionnaire as per Food and Agriculture Organization. Weight and height measurements of all children were taken using standard techniques, and nutritional status was assessed using Z scores in terms of wasting, stunting, and underweight as per the World Health Organization norms. Results: About 5.4% children were severely wasted, 10.2% children were severely underweight, and 24.7% children were severely stunted. About 22.1% children had low DD scores, 41.3% had scores indicating medium diversity, and 36.6% children had high scores for DD. Children who were severely undernourished, i.e. those whose Z scores were ?3 tended to have lower DD scores than their better-nourished counterparts for all three nutritional status indicators - weight for height, weight for age, and height for age. Conclusion: DD plays an important role in improving the nutritional status of child. Therefore, there is need to educate mothers in terms of DD to improve nutritional status of children.